Hospital site selection based on two-phase multi-criteria group decision-making method using interval-valued Fermatean fuzzy Aczel–Alsina averaging aggregation operators - Bibhuti Bhusana Meher; S. Jeevaraj (Future Business Journal)
Abstract The interval-valued Fermatean fuzzy set theory plays an essential role in modeling the problem, which involves inadequate and imprecise information in a real-life scenario. Aggregation operators play a vital role in modeling and solving any decision-making problem. By keeping these points in mind, this work first establishes a few interval-valued Fermatean fuzzy aggregation operators, such as the interval-valued Fermatean fuzzy Aczel–Alsina weighted averaging operator, the interval-valued Fermatean fuzzy ordered weighted averaging operator, and the interval-valued Fermatean fuzzy Aczel–Alsina hybrid averaging operator. Secondly, this study establishes a new modified interval-valued Fermatean fuzzy two-phase multi-criteria group decision-making method based on our proposed interval-valued Fermatean fuzzy Aczel–Alsina weighted averaging operator to solve the multi-criteria group decision-making problem involving hospital site selection. Thirdly, this study demonstrates a comparative analysis of our proposed multi-criteria group decision-making method with different approaches to verify its credibility and efficacy. Finally, this study discusses the sensitivity analysis using the weights of the criteria and shows how the result varies by changing the weights of the criteria.